The Urgency of Criminal Code Bill Ratification in Criminal Law Policy Frame on The Spreading of Pornographic Content Offence - Aldo Andrieyan Putra Makaminan; Eko Soponyono (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
Nowadays, the crime of spreading pornographic content as one form of cybercrimes has developed into a frequent offence. This offence has inflicted a lot of damage psychologically and materially for those who become the victims because, with internet access available in cyber space, the spread of pornographic materials is faster, wider, and easier to be accessed by public. The aim of this study is to review criminal law policy on the handling of pornographic content spreading offence according to the present and the future positive law. This study used normative juridical method, a method which analyzed a problem based on ius constitutum and ius constituendum. Criminal Code and Special Criminal Act such as Pornographic Act and Electronic Information and Transactions Law (UU ITE) have not clearly regulated pornographic content spreading crime in Indonesia and have not been able to countermeasure this type of crime. This problem occurs in part because regulations are applicable specifically for offence containing pornographic element, but not applicable for the spread. Criminal Code Bill needs to be ratified because the Bill regulates the offence related to pornographic contents which is suitable to the condition and issue arising in Indonesia recently. In comparison to regulations on offence related to pornographic content spreading in various countries, the author found that each country adjusts the law related to pornographic content spreading according to the type of issues they face. Thus, Indonesia also needs to make a legal product that can suppress the spread of pornographic materials.